The Poverty of Exemplification and the Richness of Musical Expressiveness – A Response to Guerreiro - Sousa, Tiago (Res Facta Nova, 2025)
Vitor Guerreiro has offered a critique of an article of mine in which I seek to demonstrate that Nelson Goodman's notion of metaphorical exemplification presents serious problems when applied to purely instrumental music. Concerning one of the issues I raise (the idea that the notion of exemplification fails to capture the expressive singularity of a purely instrumental musical work of great artistic value), Guerreiro argues that exemplification is indeed compatible with musical expressiveness. I argue that although exemplification, in the Goodmanian sense, is not incompatible with expressiveness, such a notion is not satisfactory in explaining the expressive singularity of this type of work, nor the value we attribute to it. I conclude that if we wish to maintain that a Bach prelude possesses the expressive and artistic value that we recognize in it, then we must consider such value outside of Goodman's theory, abandoning also the explanatory character of the notion of exemplification as it arises within that theory.